2015
DOI: 10.11124/jbisrir-2015-1950
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of orthopedic patient education in improving patient outcomes: a systematic review protocol

Abstract: Patient education is an essential part of practice for all healthcare professionals. In the orthopedic setting, effective patient education contributes to positive patient outcomes. Patient education is critical to ensure that patients receive appropriate information to assist in the pre-admission, peri-operative treatment and rehabilitation process for the patient. The process of patient education is essentially one where the patient comes to understand his or her physical condition and self-care using the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 24 publications
0
31
0
3
Order By: Relevance
“…Patient information plays an important role in patient contentment after surgery. Many studies have shown the positive effects of patient education and information given before surgery [17,18,35,36,44,45]. The importance of information and lack of information was made clear by the discontented participants in our study.…”
Section: Discussionmentioning
confidence: 61%
“…Patient information plays an important role in patient contentment after surgery. Many studies have shown the positive effects of patient education and information given before surgery [17,18,35,36,44,45]. The importance of information and lack of information was made clear by the discontented participants in our study.…”
Section: Discussionmentioning
confidence: 61%
“…This gap between veterinarians and pet owners in appreciation of pain emphasizes the requirement for better education and communication with pet owners pertaining to pain in various medical conditions. In human medicine, client education has been proven to improve outcomes and patient compliance for pain management . Evidence related to this field is more limited in the veterinary literature, especially in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Patient information plays an important role in patient contentment after surgery. Many studies have shown the positive effects of patient education and information given before surgery [17,18,35,36,44,45]. The importance of information and lack of information was made clear by the discontented participants in our study.…”
Section: Discussionmentioning
confidence: 64%